1998
DOI: 10.1111/j.1442-200x.1998.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated deficiency of glucocorticoids presenting with cholestasis

Abstract: Background: Isolated deficiency of glucocorticoids is characterized by elevated levels of adrenocorticotropin (ACTH) and nomial aldosterone production. It is rare for isolated deficiency of glucocorticoids to be associated with liver involvement. A case of an infant with isolated deficiency of glucocorticoids presenting with cholestasis is presented in this article. A male infant on his 39th postnatal day was referred to our hospital for evaluation of prolonged jaundice and convulsion. He had two episodes of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The presentation with hypoglycemia with or without convulsion, in addition to cholestasis was constant in all four cases and characteristic of the cases of isolated cortisol deficiency reported in the literature. [3101719] The pattern of liver enzymes and biochemical indices of cholestasis were not specific to isolated cortisol deficiency and could occur with other causes of cholestasis. Previous reports of isolated cortisol deficiency-associated cholestasis in young infants showed that gamma-glutamyl transferase was elevated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presentation with hypoglycemia with or without convulsion, in addition to cholestasis was constant in all four cases and characteristic of the cases of isolated cortisol deficiency reported in the literature. [3101719] The pattern of liver enzymes and biochemical indices of cholestasis were not specific to isolated cortisol deficiency and could occur with other causes of cholestasis. Previous reports of isolated cortisol deficiency-associated cholestasis in young infants showed that gamma-glutamyl transferase was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…[2] None of our patients had liver biopsy; however, data from the literature indicate that hepatic histological changes were not specific and showed giant cell transformation, canalicular bile stasis, Kupffer cell hyperplasia, and mononuclear cell infiltration and minimal fibrosis in portal tracts. [317] Therefore, given the availability of noninvasive hormonal tests and in the right clinical setting of cholestasis and hypoglycemia, liver biopsy is not necessary for the diagnosis of suspected cortisol deficiency in young infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated glucocorticoid deficiency (IGD) is a rare but potentially lethal hereditary disease caused by loss of function mutations of ACTH receptor gene ( 61 ). IGD-affected children have a deficient production of cortisol in the presence of markedly elevated ACTH levels and may also present with cholestatic symptoms such as jaundice, hyperpigmentation of the skin, hepatomegaly and increased levels of hepatic biomarkers in the serum ( 61 , 62 ). Cholestasis secondary to panhypopituitarism in infants has also been reported ( 63 65 ).…”
Section: Clinical Studies On Hpa Axis Dysfunctions Associated With Hementioning
confidence: 99%
“…Serum cortisol (8 a.m.) was low at <1 g/dL while serum adrenocorticotropic hormone (ACTH) was high at >1,250 pg/mL. Isolated cortisol deficiency (low cortisol, high ACTH, normal aldosterone) can cause neonatal cholestasis [1,2]. The mechanism is not known; however, cortisol has been shown to influence bile formation and enhance bile flow in animal models.…”
Section: Published Online: 18 October 2013 # Indian Society Of Gastromentioning
confidence: 99%